Analisis Kebutuhan Pengembangan E-Modul dengan Pendekatan Universal Design For Learning (UDL) pada Materi Jamur untuk Siswa Inklusi Tingkat SMA - Yolanda Azahra; Helsa Rahmatika (Lembaga Yasin AlSys, 2026)
Although the development of inclusive teaching materials and the Universal Design for Learning approach has received attention in various studies, studies that specifically discuss needs analysis for developing Universal Design for Learning-based e-modules on fungi material for senior high school students in inclusive classes remain limited. This study aims to analyze the need for developing an e-module using the Universal Design for Learning approach on fungi material for inclusive senior high school students. This study used a descriptive approach with a mixed methods design, involving one biology teacher and 34 students in one inclusive class at SMAN 9 Padang, selected through a combination of purposive sampling and total sampling techniques. Data were collected through teacher interview sheets, learning style identification questionnaires, and teaching material development needs analysis questionnaires, then analyzed descriptively using qualitative-quantitative methods. The results show that most students had mixed or multimodal learning styles at 53%, followed by kinesthetic learning styles at 20%, visual learning styles at 18%, and auditory learning styles at 9%. Students experienced difficulties in understanding fungi material because of less effective learning processes, limited relevant and applicable teaching materials, and the abstract and complex characteristics of the material. Teachers’ learning strategies, which were still dominated by lecture methods and group discussion-presentations, also had not fully accommodated the diversity of students’ learning needs. In addition, students needed electronic teaching materials that were more contextual and based on real phenomena. The conclusion of this study affirms the importance of accommodating the diversity of learning styles and special needs of students in designing biology teaching materials for inclusive classes. The implications of this study include theoretical contributions to the development of inclusive education literature and Universal Design for Learning-based teaching material design, as well as practical implications for teachers and curriculum developers in designing e-modules that are more responsive to the diversity of students’ learning needs.